Mechanical properties and lifetime predictions of dense SrTi1-xFexO3-δ (x = 0.25, 0.35, 0.5). Issue 7 (July 2017) - Oliveira Silva, R.; Malzbender, J.; Schulze-Küppers, F.; Baumann, S.; Guillon, O.
Abstract: New oxygen transport membrane materials based on SrTi1-x Fex O3-δ, synthesized through solid state reaction and processed via tape casting were characterized with respect to their mechanical behaviour via depth-sensitive indentation and ring-on-ring flexural testing. The elastic moduli obtained by indentation with 1 N load for SrTi1-x Fex O3-δ (x = 0.25, 0.35, 0.5) specimens were 147 ± 10 GPa, 123 ± 6 GPa and 158 ± 10 GPa, respectively. Fracture stress was accessed by ring-on-ring testing performed at 100 N/min and the obtained results were 92 ± 9 MPa, 117 ± 15 MPa, and 100 ± 15 MPa for SrTi0.75 Fe0.25 O3, SrTi0.65 Fe0.35 O3, and SrTi0.5 Fe0.5 O3 respectively. Ring-on-ring tests conducted at different loading rates gave access to subcritical crack growth sensitivity and aided the prediction of the materials' lifetime through stress-time-probability diagrams, where SrTi1-x Fex O3-δ (x = 0.25, 0.35, 0.5) may resist for 1 year with a failure probability of 0.1% at least 15 MPa, 22 MPa, and 12 MPa respectively.